2020
DOI: 10.3847/1538-4357/aba19a
|View full text |Cite
|
Sign up to set email alerts
|

The Formation of a Stellar Association in the NGC 7000/IC 5070 Complex: Results from Kinematic Analysis of Stars and Gas

Abstract: We examine the clustering and kinematics of young stellar objects (YSOs) in the North America/Pelican Nebulae, as revealed by Gaia astrometry, in relation to the structure and motions of the molecular gas, as indicated in molecular-line maps. The Gaia parallaxes and proper motions allow us to significantly refine previously published lists of YSOs, demonstrating that many of the objects previously thought to form a distributed population turn out to be nonmembers. The members are subdivided into at least six s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 125 publications
5
56
0
Order By: Relevance
“…NAP members (white pluses) identified in this work overplotted on a three-color image of the North America Nebula created in the same way as in Figure 1. The color-coded open circles are members of the individual kinematic groups identified by Kuhn et al (2020). The color-coded large ellipses show the boundaries of the kinematic groups depicted in this work to group the YSOs without reliable astrometric measurements.…”
Section: The Effect Of Spectral Veiling On Stellar Classificationmentioning
confidence: 96%
See 4 more Smart Citations
“…NAP members (white pluses) identified in this work overplotted on a three-color image of the North America Nebula created in the same way as in Figure 1. The color-coded open circles are members of the individual kinematic groups identified by Kuhn et al (2020). The color-coded large ellipses show the boundaries of the kinematic groups depicted in this work to group the YSOs without reliable astrometric measurements.…”
Section: The Effect Of Spectral Veiling On Stellar Classificationmentioning
confidence: 96%
“…The white dashed circle indicates the approximate boundary of the H II region (Wendker et al 1983). All the YSO candidates in the field are shown as open circles, magenta for those with infrared excess (Rebull et al 2011) and green for those identified with Gaia (Kuhn et al 2020). Our spectroscopically confirmed YSOs are shown as yellow filled circles.…”
Section: Palomar/norris Spectramentioning
confidence: 99%
See 3 more Smart Citations